An Unknown World: The Academic Experiences of Korean Immigrant Students at Two Universities in Toronto, Canada - Kim, Eun Gi (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2022)
Although the participation of immigrant students from diverse cultural backgrounds continues to increase in Canadian universities, there is still a lack of a good understanding of their experiences. This study compared the experiences of nine Korean immigrant students in the sciences and social sciences at two Toronto-based universities and the support resources they utilized. Using Reason’s (2009) persistence framework, different aspects of student experiences, including the transition from high school to university and their academic studies, were examined through semi-structured focus groups and interviews. Research participants commonly had difficulties adjusting to Canadian universities and encountered linguistic difficulties throughout their lecture participation and assessment completion that hindered their persistence toward their goal of graduation. The participants varied in the difficulties they encountered with the disciplinary natures of the sciences and social sciences throughout their studies. The participants developed strategies of audio-recording lectures, reaching out to their peers and teaching staff, and using online resources to overcome the challenges. Differences in participant experiences between the two universities appeared regarding Korean student groups, which they found as the most beneficial source of support. Suggestions are made to better support the experiences of immigrant students in Canadian universities.